MENGAKARKAN TOLERANSI BERAGAMA DI INDONESIA DALAM TERANG SURAT APOSTOLIK PATRIS CORDE - Frans Richard; Cornelius Arnoltus; Petrus Bine Saramae (LP2M STIKPAR Toraja, 2024)
Indonesia as a diverse country is vulnerable to problems of intolerance. Based on existing data, it appears that tolerance crisis is still occurring in Indonesia. Pope Francis' Apostolic Letter of Pastris Corde can be an offer in dealing with the current tolerance crisis. This research aims to examine the tolerance crisis in Indonesia and to build a theological reflection in the light of the Apostolic Letter of Patris Corde. The research method used in this research is qualitative research method using library research as a technique for collecting data related to the topic. Literature study is applied by reading, reviewing, and recording references or literature related to the subject matter. The results of the research were then written in a systematic and logical theoretical thinking framework. The results of this research show that the acts of intolerance still frequently occur in Indonesia, therefore Pope Francis through his apostolic letter Patris Corde invites everyone to imitate Saint Joseph in facing existing crises, including the tolerance crisis in Indonesia. The virtues of Saint Joseph that can be imitated are humility, love, peace, solidarity, and care.